Interactions of ruthenium coordination cubes with DNA - Barry, Nicolas P.E.; Abd Karim, Nurul H.; Vilar, Ramón; Therrien, Bruno (My University, 2009)
The interactions of four octacationic ruthenium coordination cubes with duplex and quadruplex (telomeric and c-myc) DNA have been studied by FID and SPR, showing these cubes to bind strongly to tetrastranded DNA structures.